Financial Analysis and Risk Assessment of Grouper Cage Culture Systems in Negros Occidental - Abeto, Mario N. (JPAIR Multidisciplinary Research, 2010)
The study assessed the financial and risk exposures of grouper cage farming in Negros Occidental. Through survey questionnaire administered to 68 grouper cage growers in the four grouper growing areas in Binalbagan, Himamaylan, Hinigaran, and Sagay, the study appraised the feasibility and viability of grouper cage farming and established a benchmark for cage farmers in making crucial investment decisions in mariculture development. Data on the financial analysis and risk indicators were analyzed using the mean, range, and standard deviation. Data were presented by province and by LGUs. Results of the study showed that a return of investment (ROI) of 29.95% is realized which is far behind the ROI of some aquaculture projects like shrimp hatchery (40%) and grouper culture in ponds (82%). Likewise, the analysis showed a payback period of 3.88 years which seems not economically feasible as it posed a high risk of payment default when capital is sourced from banks. It is also noted that the length of the cropping cycle is prolonged from normally 8 months to 10.6 months average and had a long recovery period (3 years and 6 months) for the capital invested. Though the project is not financially attractive in some variables, the project is still feasible in most important variables like profit per crop (Php26,541.76) and profit margin (29.91%). Among the four LGUs, Binalbagan showed the best performance in both financial analysis and risk indicators indicating the area is attractive for mariculture project. Â Keywords - financial analysis, risk assessments, grouper cage culture, risk exposure indicators